KAJIAN SEMIOTIKA VISUAL PADA KARYA FOTOGRAFI “THE UNTOUCHABLES” ERIK RAVELO - Nanda Nini Anggalih; Wening Hesti Nawa Ruci (Narada : Jurnal Desain dan Seni, 2022)
Erik Ravelo is an artist who produces controversial, vulgar, and offensive photography works of various parties whose figures are 'as if' involved in his various works. In this study, Erik Ravelo's work as one of the visual communication design that can produce signs or messages analyzed through a semiotic approach to explore the meaning of each sign. Researcher uses a semiotic approach from Charles Pierce Sanders that focuses on the idea of triadic semiotics (three basic elements), namely representamen, interpretantts and objects. The results obtained in the form of three types of signs classified as icons, indexes, and symbols.